¡Que suene una cumbia infinita! DJs, radio y tecnocumbia: una etnografía sobre prácticas sonoras entre jóvenes del pueblo Misak (Colombia) - Martínez Peña, Oscar Giovanni (2022)
The anthropological discussion about young indigenous populations and their current practices suggests thinking of them in a complex framework of tensions to problematize and deessentialize the ways of being indigenous, in addition to questioning the place of enunciation of the researcher. In this ethnographical work, I examine the ways in which the youth of the Misak People in Cauca, Colombia, organize and redefine sound ontologies through radio, DJs and tecnocumbia groups. I research with “those who make sound”- a native category that refers to people who produce and manipulate sound, in this case, young men. In the intersubjective experience as a white-mestizo anthropologist and musician, I investigate the ways of listening, feeling and knowing through sound, valuing learning processes and sound as a place of knowledge (acoustemology), in relation to overlapping territorialities, bodies and indigenous cosmologies in the neoliberal context of an exacerbated and violent capitalism in the first decades of the 21st century. I suggest the notion of techno-sonic formations as a way of interpreting, through ethnography, the sound frictions immersed in networks of sonic-musical practices between humans, extrahuman beings, and electronic and digital technologies through ethnography. In this research, the techno-sonic formations account for alternative forms of indigeneity to the "indigenous voice", built on global connections that signify tecnocumbia as Andean Cosmopolitanism. I understand the growing strength of this techno-sonic formation as a possibility of territorial expansion for Misak youngsters in the face of historical dispossession, the limitation of indigenous territories and the dynamics of mobility in the region in which they face racialized imaginaries. In this way, Misak youth agency their corporeality and vocality, with diverse skills and mastery of various sound technologies to subvert such stereotypes, building a modern indigeneity at the technological and global forefront. This implies learning processes in the creation and production of music that refer to intersensory experiences, bright colors and sounds, intense emotions and effects on the body. In this way, they convert sound materialities into merchandise as a symbolic capital that allows them to claim a place of existence in a world, where the body and its abilities are their last capital for negotiation.